Amine-Free O-Sulfonylation by a Combination of 4-Methylpyridine N-Oxide Catalyst with 4Å Molecular Sieves - Yoshida, Keisuke; Matsumoto, Yuma; Masuda, Juo; Kitagaki, Shinji (Synlett, 2022)
An amine-free sulfonylation of various alcohols was developed that uses 4-methylpyridine N-oxide in the presence of 4Å molecular sieves at room temperature. This mild method gives various sulfonylated products in high yields, and can be applied to base-sensitive substrates.
Keywords: sulfonylation; methylpyridine oxide; alcohols; molecular sieves; sulfonates; mesylation